MEMBANGKITKAN KEMBALI KARMA PHALA SEBAGAI PILAR KEYAKINAN AGAMA HINDU - I WAYAN SAPTA WIGUNADIKA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Hinduism teaches about the five forms of faith or belief called panca sradha. One of them is Karma in its narrow meaning is deed, widely is the law of cause or effect of all actions called karma phala. The law of karma has a universal nature, in the sense that all beings will be subject to the law of karma, and all deeds will surely get the result. Karma comes from thoughts, speech and deeds. So good a bad deed which although still limited to the mind will also get the result. This life inherits our own karma. We are the makers of karma for ourselves, karma befall anyone and karma is eternal law, because karma is an element of causal law. The doctrine of nutmeg karma that becomes the pillar of Hindu religion must be raised again. If the teachings of nutmeg karma are not taught it is most likely that the doctrine will always be a meaningless utterance. Understanding the karma of nutmeg is the eternal law of old, now and then the peace will come true. In the upanisads described all deeds will get results, both deeds are good for society and the act is detrimental to society. Both of these will gain good results both in the world and in the afterlife.